Preventing genocide in Gaza - Sater, James; Vella de Fremeaux, Patricia; Attard, Felicity; Calleja, Isabelle; Cassar, Valentina; Grech, Omar; Khakee, Anna; Pennisi, Angela (Plurimondi, 2025)
This contribution is published courtesy of Times of Malta.